Impacts of herbivory by ecological replacements on an island ecosystem. Issue 9 (27th December 2021) - Moorhouse‐Gann, Rosemary J.; Vaughan, Ian P.; Cole, Nik C.; Goder, Martine; Tatayah, Vikash; Jones, Carl G.; Mike, Daevid; Young, Richard P.; Bruford, Michael W.; Rivers, Malin C.; Hipperson, Helen; Russo, Isa‐Rita M.; et al.
Abstract: The use of ecological replacements (analogue species to replace extinct taxa) to restore ecosystem functioning is a promising conservation tool. However, this approach is controversial, in part due to a paucity of data on interactions between analogue species and established taxa in the ecosystem. We conducted ecological surveys, comprehensively DNA barcoded an ecosystem's flora and inferred the diet of the introduced Aldabra giant tortoise, acting as an ecological replacement, to understand how it might have modified island plant communities on a Mauritian islet. Through further dietary analyses, we investigated consequential effects on the threatened endemic Telfair's skink. Dietary overlap between tortoises and skinks was greater than expected by chance. However, there was a negative correlation between tortoise and skink preferences in herbivory and minimal overlap in the plants most frequently consumed by the reptiles. Changes in the plant community associated with 7 years of tortoise grazing were characterised by a decrease in the percentage cover of native herbs and creepers, and an increase in the cover of an invasive herb when compared to areas without tortoises. However, tortoise dietary preferences themselves did not directly drive changes in the plant community. Tortoises successfully dispersed the seeds of an endemic palm, which in time may increase the extent of unique palm‐rich habitat. We found no evidence that tortoises have increased the extent of plant species hypothesised to be part of a lost Mauritian tortoise grazed community. Synthesis and applications . Due to a negative correlation in tortoise and skink dietary preferences and minimal overlap in the most frequently consumed taxa, the presence of tortoises is unlikely to have detrimental impacts on Telfair's skinks. Tortoise presence is likely to be beneficial to skinks in the long term by increasing the extent of palm‐rich habitat. Although tortoises are likely to play a role in controlling invasive plants, they are not a panacea for this challenge. After 7 years, tortoises have not resurrected a lost tortoise grazed community that we hypothesise might have existed in limited areas on the islet, indicating that further interventions may be required to restore this plant community. Abstract : Due to a negative correlation in tortoise and skink dietary preferences and minimal overlap in the most frequently consumed taxa, the presence of tortoises is unlikely to have detrimental impacts on Telfair's skinks. Tortoise presence is likely to be beneficial to skinks in the long term by increasing the extent of palm‐rich habitat. Although tortoises are likely to play a role in controlling invasive plants, they are not a panacea for this challenge. After 7 years, tortoises have not resurrected a lost tortoise grazed community that we hypothesise might have existed in limited areas on the islet, indicating that further interventions may be required to restore this plant community. Résumé: L'utilisation de remplacements écologiques (espèces analogues pour remplacer les taxons éteints) pour restaurer le fonctionnement d'un écosystème est un outil de conservation prometteur. Cependant, cette approche est controversée, en partie à cause d'un manque de données sur les interactions entre les espèces analogues et les taxons présents dans l'écosystème. Nous avons mené des études écologiques, codé l'ADN de la flore d'un écosystème et déduit le régime alimentaire de la tortue géante d'Aldabra, espèce introduite agissant comme un remplacement écologique, pour comprendre comment elle aurait potentiellement modifié les communautés végétales insulaires sur un îlot mauricien. Grâce à d'autres analyses alimentaires, nous avons étudié les effets résultants sur le scinque de Telfair, une espèce endémique menacée. Le chevauchement entre l'alimentation des tortues et les scinques était plus important que prévu. Cependant, il y avait une corrélation négative entre les préférences des tortues et des scinques au niveau de l'herbivorie et un chevauchement minime pour les plantes les plus fréquemment consommées par ces reptiles. Les changements dans la communauté végétale associés à sept années de broutage des tortues ont été caractérisés par une diminution du pourcentage de couverture d'herbes et de plantes grimpantes indigènes, et une augmentation de la couverture d'une herbe envahissante par rapport aux zones sans tortues. Cependant, les préférences alimentaires des tortues elles‐mêmes n'ont pas directement entraîné de changements dans la communauté végétale. Les tortues ont réussi à disperser les graines d'un palmier endémique, ce qui, avec le temps, pourrait augmenter l'étendue de l'habitat riche en palmiers. Nous n'avons trouvé aucune preuve que les tortues ont augmenté l'étendue des espèces végétales supposées faire partie d'une communauté végétale disparue qui existait dû au broutage des tortues mauriciennes. Synthèse et applications . En raison d'une corrélation négative dans les préférences alimentaires des tortues et des scinques et d'un chevauchement minimal dans les taxons les plus fréquemment consommés, il est peu probable que la présence de tortues ait des effets néfastes sur les scinques de Telfair. La présence de tortues est susceptible d'être bénéfique pour les scinques à long terme en augmentant l'étendue de l'habitat riche en palmiers. Bien que les tortues soient susceptibles de jouer un rôle dans le contrôle des plantes envahissantes, elles ne sont pas une panacée pour ce défi. Après sept ans, les tortues n'ont pas ressuscité la communauté végétale disparue qui existait dû au broutage des tortues endémique qui, selon nous, aurait pu exister dans des zones limitées de l'îlot, ce qui indique que d'autres interventions pourraient être nécessaires pour restaurer cette communauté végétale.